2010
DOI: 10.4317/medoral.15.e459
|View full text |Cite
|
Sign up to set email alerts
|

Oro-facial aspects of leprosy: Report of two cases with literature review

Abstract: Leprosy is a chronic infectious disease affecting primarily the skin, peripheral nerves, respiratory system and the eyes. Leprosy induces various types of clinical presentation affecting the patient´s immune response. Cellmediated immunity is considered to be the crucial defence against the disease and the magnitude of this immunity defines the extent of the disease. The article presents two case reports of manifestations of leprosy in the oro-facial region, with a brief review of various other important oro-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 7 publications
1
26
0
3
Order By: Relevance
“…Although relatively uncommon, for dentists, cranial nerve involvement is an important feature of leprosy. This study found the trigeminal nerve and the facial nerve were the most commonly affected nerves, which is similar to previous studies and reports 15,16 . This may have specific implications for the teeth.…”
Section: Discussionsupporting
confidence: 93%
“…Although relatively uncommon, for dentists, cranial nerve involvement is an important feature of leprosy. This study found the trigeminal nerve and the facial nerve were the most commonly affected nerves, which is similar to previous studies and reports 15,16 . This may have specific implications for the teeth.…”
Section: Discussionsupporting
confidence: 93%
“…A case of oral lesion associated with leprosy has been described elsewhere in a borderline tuberculoid Ada Derm Venereol 91 (BT)-MB patient with papulo-nodular lesions in the centre of the hard palate, by histopathological findings (5). However, oral mucosa lesions are not normally found in PB patients (5,6), and when they are present, manifestations have been described exclusively in the tuberculoid and borderline forms in the reactional state, with few scientific studies and poorly characterized descriptions (7).…”
mentioning
confidence: 95%
“…Facial manifestations in leprosy are similar to lesions in other parts of skin, and some of these changes can result in specific deformities for this site (Ghosh et al , ; Naik et al , ). Oral mucosal involvement in leprosy may result from hematogenous or lymphatic dissemination of M. leprae , or be secondary to nasal lesions (de Abreu et al , ; Motta et al , ).…”
Section: Orofacial Manifestations In Leprosymentioning
confidence: 99%
“…Facial lesions can occur in any leprosy form and follow the spectrum of clinical manifestations, varying from localized, well‐defined, hypopigmented macules or plaques to multiple nodules coalescing in plaques on the forehead, ears, nose, and lips (Pavithran, ; Naik et al , ; Salgado and Barreto, ). In advanced stages, patients usually present loss of eyebrow hair and eyelashes, diffuse thickening of the facial skin, and deepening of natural facial lines characterizing the ‘leonine facies’ (Ghosh et al , ; Salgado and Barreto, ) (Figure a–c).…”
Section: Orofacial Manifestations In Leprosymentioning
confidence: 99%
See 1 more Smart Citation